2008
DOI: 10.1007/s00227-008-0941-z
|View full text |Cite
|
Sign up to set email alerts
|

Tropical fishes in a temperate sea: evolution of the wrasse Thalassoma pavo and the parrotfish Sparisoma cretense in the Mediterranean and the adjacent Macaronesian and Cape Verde Archipelagos

Abstract: The northeastern Atlantic and the Mediterranean Sea share geological histories and display great faunal aYnities. The majority of the Mediterranean species have Atlantic origins, with a few species with tropical aYnities. These include the parrotWsh Sparisoma cretense and the wrasse Thalassoma pavo that are restricted to the subtropical northeastern Atlantic, the Macaronesian archipelagos (Azores, Madeira, and Canaries) and the southern Mediterranean. The Pleistocene glaciations have been described as having d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 37 publications
0
11
1
Order By: Relevance
“…Our view differs from that of previous authors, who suggested that 'the drop of sea temperatures : : : that occurred during the Pleistocene probably resulted in mass extinctions' (of fishes) and so 'most of the organisms now present would have reached the Azores in the last 17,000 years' (Santos et al 1995). Our reasoning also contradicts the conclusions of Domingues et al (2008), who stated that 'persistence of : : : S. cretense in the Azores archipelago during the Pleistocene glaciations is difficult to admit'. Moreover, the very abundant and well-studied MIS 5e (i.e.…”
Section: Molluscacontrasting
confidence: 99%
See 2 more Smart Citations
“…Our view differs from that of previous authors, who suggested that 'the drop of sea temperatures : : : that occurred during the Pleistocene probably resulted in mass extinctions' (of fishes) and so 'most of the organisms now present would have reached the Azores in the last 17,000 years' (Santos et al 1995). Our reasoning also contradicts the conclusions of Domingues et al (2008), who stated that 'persistence of : : : S. cretense in the Azores archipelago during the Pleistocene glaciations is difficult to admit'. Moreover, the very abundant and well-studied MIS 5e (i.e.…”
Section: Molluscacontrasting
confidence: 99%
“…The finding of fossil pharyngeal plates belonging to S. cretense in MIS 5e sediments does not necessarily preclude the hypothesis that this species locally disappeared during the Last Glaciation, only to recolonize the archipelago post-glacially. Nevertheless, we consider it more plausible to argue that such extirpation did not happen, taking into consideration the facts that: (1) detailed studies on the Azorean MIS 5e and recent marine molluscs showed that the drop of the SSTs during the Last Glaciation only affected two groups of species: the tropical species that reached the Azores probably during a 'window of opportunity' associated with the final phase of Termination 2, and bivalve species associated to fine-sand sediments; both groups were extirpated (Ávila et al 2008a, b, 2009b, 2015b); (2) as temperature is known to play a key role on marine fish species biology (Pepin, 1991;van der Kraak & Pankhurst, 1997;Pankhurst & Porter, 2003;Dolomatova et al 2013;Poloczanska et al 2016) and, in light of previously published theories (Ávila et al 2008a, 2009b, 2015b), the drop of SSTs was not sufficient enough to severely affect the survival, growth and reproduction of the temperate parrotfish S. cretense in the Azores during the Last Glacial episode; and (3) if S. cretense was a post-glacial colonizer of the Azores, the genetic diversity of the Azorean populations should be low in comparison to southern Madeiran populations (postulated to have been unaffected by the drop of SSTs); that is not the case, however, as pointed out by Domingues et al (2008). Combining our palaeontological data with ecological and genetic data from other authors (Abecasis et al 2008;Afonso et al 2008;Domingues et al 2008), we therefore believe the most plausible scenario is the survival of most (if not all) temperate and subtropical fish species in the Azores during the Last Glacial episode, as long as their ecological traits were not constrained to sandy habitats.…”
Section: Molluscamentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the presence of haplotype CC-A6.1 in Western Greece and haplotypes CC-A3.2 and CC-A52.1 in Eastern Turkey indicates that these populations might have survived at least the most recent glacial peak. Consequently, the northern part of the Eastern Mediterranean and Western Peloponnese seems to have acted as warm refugia for marine species at that time, as has already been suggested for fishes (Domingues et al, 2008). This hypothesis could explain the genetic structure currently seen in Turkey, with a strong westward decline in haplotype diversity and a high variability in the frequency of CC-A3.1 between adjoining sites.…”
Section: Evolutionary Historymentioning
confidence: 63%
“…These archipelagos share similar geomorphological traits; they are all volcanic in origin, and although there is no general consensus, most are thought to be the result of several geologic hotspots (Carracedo, 2001). They have a unique biogeography: all native flora and fauna reached the archipelagos via long-distance dispersal from adjacent continental areas (Whittaker & Ferna´ndez-Palacios, 2007) or, in some circumstances, adjacent archipelagos (Domingues et al, 2008). Marine biotas of the different archipelagos are interconnected via oceanic currents; surface currents generally (but not always) move from the Azores towards Madeira and the Canary Islands (Morton et al, 1998).…”
Section: Introductionmentioning
confidence: 99%